A case study evaluation of edible plants curriculum implemented in an elementary school - Graves, Leila, author; Hughes, Harrison, advisor; Balgopal, Meena, advisor; Bunning, Marisa, committee member; Krishnan, Sarada, committee member (Colorado State University. Libraries, 2014)
The main purpose of this study was to describe elementary teachers' attitudes and perceptions toward plant science. The secondary purpose was to create an edible plant curriculum as a vehicle for integrating STEM and 21st Century skills into Common Core Content. Results indicate that teachers and STEM coordinators did find the curriculum to be effective in teaching the interdisciplinary standard-based and inquiry based content and skills targeted. Additionally, the curriculum development process produced a hybrid design framework that facilitated the creation of life science content as a vehicle for integrating STEM into common core content. However, several significant barriers will need to be overcome with regard to the teachers', STEM coordinators' and administrators' perception that plant science and nutrition literacy are "special" content activities versus important STEM content.
Keywords: common core content; curriculum development; inquiry based; interdisciplinary; standard-based; STEM